Economical bluetooth low energy-based telemetry system with combined data processing method for long-term laboratory animal monitoring for biological rhythm research. (4th March 2021) - Luo, Hua; Cheng, Shuting; Jiang, Zhou; Hou, Wang; Wang, Zhengrong
ABSTRACT: A telemetry system based on Bluetooth Low Energy (BLE) was constructed to simultaneously collect locomotor activity and physiological signals of small animal cohorts for circadian rhythm experiments; it consists of miniature transmitters and mobile phone with customized App. The continuous sampling signals obtained from the 3-axis acceleration and temperature sensors in the transmitters are sent to the mobile phone in real-time through Internet of Things (IoT) for temporary storage and then imported into the computer for summary and rhythm analysis by the general open-source mathematical software. Unlike expensive and complicated commercial telemetry systems with industrial wireless standards, no special data receivers and software are needed. In our validation experiment, six rats were divided into two groups under natural dark and light-dark cycles. For two consecutive weeks, the transmitter mounted on the head of the rat-recorded locomotor activity, skin temperature, and ambient temperature of each rat at a frequency of 6 Hz. After processing with Local Weighted Regression Scatter Smoothing (LOWESS) and Fast Fourier Transform (FFT) filtering, single cosinor and multi-components cosinor were then used to assess and characterize the circadian rhythm. The results showed that the rhythm values of the two groups of rats coincided with the corresponding light-dark cycle, and that the system was robust to data loss and error from BLE communication failures. Therefore, the proposed system provides a light-weight framework for long-term circadian rhythm monitoring in free-moving rodents to further simplify and promote experimental chronobiology animal studies.